LabVIEW- Based Leaching Tank Process Control System for Laterite Nickel Ore Processing on a Lab-Scale Basis - Afandy, Moh; Abdul Haris Mubarak; Muhammad Ikbal Rianto; Syahril M (Jurusan Teknik Elektro Universitas Andalas, 2025)
This study successfully designed and implemented a LabVIEW-based nickel laterite ore leaching process control system on a laboratory scale. This system integrates key hardware components such as Arduino Mega 2560, temperature sensor, volume sensor, jet bubble reactor, and LabVIEW-based user interface that allows automatic and real-time monitoring and control of process parameters. The calibration results showed high accuracy, with temperature measurement error values ​​of 0.04% and 0.015% compared to the calibrator. Volume measurements under five test conditions produced error values ​​ranging from 0.023% to 0.066%, with the best accuracy shown by readings via the LabVIEW HMI. Leaching process testing was carried out using variations in citric acid concentrations. The resulting filtrate volume showed a decrease from 173 mL at a concentration of 0.5 mol to 8 mL at a concentration of 2 mol, indicating that the higher the solution concentration, the greater the viscosity of the solution, thereby inhibiting mass transfer. The application of jet bubble technology has been shown to increase the efficiency of mixing and contact between the leaching solution and the ore, which accelerates the leaching process. Overall, the system shows high stability, accuracy, and reliability for laboratory scale applications. This system is considered suitable for use as a learning medium, an initial simulation tool for the APAL (Atmospheric Pressure Acid Leaching) process, and a means of supporting research in the development of efficient, energy-saving, and environmentally friendly nickel extraction technology.